Administrative Authority of National Park Management in the Protection of Conservation Areas: Kewenangan Administratif Pengelola Taman Nasional dalam Perlindungan Kawasan Konservasi - Saputra, Aldo; Fauzani Raharja, Ivan (Fakultas Hukum Universitas Jambi, 2026)
Forest and land encroachment within Kerinci Seblat National Park continues to pose a significant threat to the sustainability of conservation functions, ecosystem integrity, and biodiversity. This issue underscores the importance of the administrative authority exercised by conservation area managers in protecting forest areas from various forms of disturbance. This study aims to analyze the administrative authority of Kerinci Seblat National Park management in the protection of conservation areas and to identify the obstacles affecting the effectiveness of its implementation. The research employs an empirical legal method using statutory and field approaches. Data were collected through interviews with national park management officials, law enforcement officers, and local communities residing around the conservation area, and subsequently analyzed qualitatively. The findings reveal that the authority of national park management is derived from the attribution and delegation of powers granted by the central government in the fields of forestry and natural resource conservation. In practice, such authority is primarily exercised through protection, supervision, prevention, and security functions, while criminal enforcement measures are carried out in coordination with competent law enforcement agencies. The effectiveness of this authority remains constrained by several factors, including limited human resources, the vast scope of the supervised area, difficult geographical conditions, low levels of legal awareness among local communities, and weak inter-agency coordination. The novelty of this study lies in the formulation of a model for strengthening the administrative authority of national park management through the integration of area supervision, cross-sectoral coordination, and community empowerment as instruments for sustainable conservation area protection. This model positions conservation area protection as an integral component of administrative accountability grounded in the principles of good governance.